An Overview of Indian Stock Market in Global Recession - Jain, P. K (Journal of Commerce and Trade, 2009)
Recession can be defined as an extended period of significant decline in economic activity including negative Gross Domestic Product (GDP) growth. After the dark night, sun rises. So investors should keep patience into his mind and should wait for the market to come out from the economic recession because in past investors got more than their losses.